Impact of weather parameters on alternaria blight of Indian mustard [(Brassica juncea (L.) Czern. & Coss.)] - Punia, Rakesh; Kumari, Pavitra; Kumar, Anil; Rathi, AS; Avtar, Ram (Bangladesh Journal of Botany, 2021)
Progression of Alternaria blight disease was measured on two susceptible Indian mustard varieties viz., RH 30 and RH 0749 sown at three different dates. The maximum increase in disease severity was recorded between first weeks of February and last week of February. During this period, the maximum and minimum temperature, relative humidity at morning and evening, average vapour pressure of morning and evening, maximum and bright sunshine hours and wind speed were higher, which resulted in congenial conditions for severe infection by the pathogen. The disease severity was positively correlated with maximum and minimum temperature, average vapour pressure, wind speed, sunshine hours and evaporation, while relative humidity and rainfall negatively correlated with Alternaria blight on both the varieties. A maximum value of area under disease progress curve was observed on cultivar RH 30 (651.1 cm2) as compared to RH 0749 (578.9 cm2), when crop was sown on 9th November.